Green tea (Cammellia sinensis) attenuates ventricular remodeling after experimental myocardial infarction - Lustosa, Beatriz B [UNESP]; Polegato, Bertha [UNESP]; Minicucci, Marcos [UNESP]; Rafacho, Bruna [UNESP]; Santos, Priscila P [UNESP]; Fernandes, Ana Angélica [UNESP]; Okoshi, Katashi [UNESP]; Batista, Diego [UNESP]; Modesto, Pamela [UNESP]; Gonçalves, Andrea [UNESP]; Pereira, Elenize J [UNESP]; Pires, Vanessa [UNESP]; et al. (Elsevier, 2016)
Background Considering the high morbidity and mortality after myocardial infarction (MI), the study of compounds with potential benefits for cardiac remodeling is reasonable. Green tea (GT) (Cammellia sinensis) is the most consumed beverage in the world. The potential action mechanisms of GT include anti-inflammatory, anti-apoptotic, antioxidant, and lipid-lowering properties. Objective This study analyzed the effects of GT on cardiac remodeling following coronary occlusion in rats. Methods Male Wistar rats were divided into four groups: control (C), control green tea (GT), myocardial infarction (MI), and myocardial infarction and green tea (MI–GT). GT and MI–GT were fed with standard chow with 0.25% Polyphenon 60 (Sigma-Aldrich Canada, Oakville, ON, Canada). After 3 months of observation, echocardiographic and isolated heart study, oxidative stress, energy metabolism, serum lipids, extracellular matrix, and apoptosis were evaluated. Results GT reduced cardiac hypertrophy and improved systolic and diastolic dysfunction. Concerning oxidative stress, GT reduced protein carbonyl, increased Nrf-2, and restored antioxidant enzyme activity to the control pattern. Energy metabolism was affected by MI that presented with lower fatty acid oxidation and accumulation of triacylglycerol, increased serum lipids, impairment of the citric acid cycle, and oxidative phosphorylation. GT stimulated the glucose pathway and mitochondrial function after MI by increasing pyruvate dehydrogenase, Complex I, ATP synthase, and glycogen storage. In addition, MI changed the extracellular matrix including MMP-2 and TIMP-1 activity and increased apoptosis by 3-caspase, all of which were attenuated by GT. Conclusion GT attenuated cardiac remodeling after MI, associated with improvement in systolic and diastolic dysfunction. Oxidative stress, energy metabolism, apoptosis, and extracellular matrix alterations are all potential mechanisms by which GT may take part.
Keywords: Antioxidant; Cardiac remodeling; Green tea; Myocardial infarction